The effect of some elements of climate and its relationship to the cultivation of the cotton crop in the central governorates of Iraq (Journal of the College of Basic Education, 2022)
This study aims to investigate the productivity of cotton crop in the central governorates of Iraq during the period (2007-2017), with the aim of uncovering the reality of production for cotton cultivation and production in the central governorates (Baghdad, Babil, Wasit, and Qadisiyah), and discussed some elements Climate influencing the cultivation of the cotton crop The research discussed studying the effect of some elements of the climate, especially the maximum and minimum temperatures, wind speed, relative humidity, and the amount of evaporation, in order to know the reality of geographical distribution in the selected central governorates of IraqThe results of standard deviation state that the variation of areas, production, and average productivity in the central governorates during the period (2010-2019). The study showed that the area cultivated with the cotton crop in the central governorates was concentrated in Babil governorate with a standard degree (1.20), then followed by a central governorate with a standard degree (0.41), while there was a dispersion in the area of ​​Baghdad and Qadisiyah governorates with a standard degree (-1.02, -0.5), respectively. As for the production of the cotton crop, the concentration in Wasit governorate reached the standard degree (0.84), then came Baghdad governorate (0.5) and Babil governorate (0.0), while the dispersion in Qadisiyah governorate reached the standard degree (-1.41). As for productivity, it concentrated in the governorate. Baghdad and the standard degree of productivity was recorded. There was a clear dispersion in the governorates (Qadisiyah, Wasit, Babil), which recorded (0.4-0.9, -1.1), respectively, while the governorate of Baghdad achieved the highest concentration rate of (1.41) due to the high average yield per dunum of the cotton crop. To use the necessary supplies of improved fertilizers and seeds, and to seek the help of economic research and studies centers, which would help in developing production and productivity This researcher highlighted the variation in production and production area in some central governorates of Iraq, as well as diagnosing the percentage of concentration and dispersion of the cotton crop during the study period, and finally, the study came out with some results and recommendations necessary to preserve the cultivation of the cotton crop in the future for future generations